2002
DOI: 10.1115/1.1502669
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Stochastic Drill-String Vibrations

Abstract: Lateral vibrations of drill-strings used in oil well operations are considered. A finite elements based discretization procedure leads to a nonlinear dynamic system which is used to represent the drill-string inertia and stiffness characteristics, as well as the elasticity of the wall of the well. Due to the erratic pattern and the uncertainty of the forces at the drill-bit, a stochastic dynamics approach is adopted in investigating the problem. The method of statistical linearization is used, and expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The equations of equilibrium of moments applied to the bit are as follows [9,19] vector connecting point C with the G point (Fig. 5).…”
Section: Whirling Of Ellipsoidal Bits On a Plane Uneven Bottom Of A Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The equations of equilibrium of moments applied to the bit are as follows [9,19] vector connecting point C with the G point (Fig. 5).…”
Section: Whirling Of Ellipsoidal Bits On a Plane Uneven Bottom Of A Bmentioning
confidence: 99%
“…The backward whirling is believed to randomly happen to some degree in 40% of all wells [1]. In the majority of cases, previous studies of this dynamic process have concentrated primarily on assumption that in whirling the rotating drill bit is compressed to the bore-hole wall and is rolling on its surface [2][3][4][5][6][7][8][9][10]. But in our opinion, a prominent phase of this effect proceeds at the initial stage of its generation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, nonlinear and time-domain modeling solutions have become possible (Spanos et al 2002). This is critical to achieve the required level of accuracy to make meaningful contributions to drilling system behavioral prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their values, the analysis results have shown that the system can be stable or undergo forward or backward whirl. Spanos et al [21] and Ritto et al [22] underline that the uncertainty is inherent in the properties of parameters determining the drilling processes, therefore, the stochastic nature of the bit rock interaction should be taken into consideration. General questions of friction influence on deep hole drilling processes are outlined by R. Samuel [23].…”
Section: Introductionmentioning
confidence: 99%